Social and Educational Context of the Poverty of People with Disabilities in Poland - Janiszewska-Nieścioruk, Zdzisława (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The article points out the high complexity and multidimensionality of the hot social issue of poverty as well as the related unemployment, and the precariousness of people with disabilities in Poland. The author notes that despite the currently promoted pro-inclusion activities and solutions for their benefit in connection with the implementation the assumptions of the Convention on the Rights of Persons with Disabilities in Poland, with insufficient support, these problems may multiply and aggravate the disability and special needs of these people. People with disabilities still too often live in conditions of poverty that have a negative impact on their development and functioning in all spheres or areas of social life, as well as in the open labour market. In the process of compensating for the shortcomings related to having been brought up in a poor family, education has a significant role to play. Therefore, the author stresses its significant importance for the process of equalizing educational opportunities for children, as well as for the weaknesses noticed in its space, which hinder this process. The author pays equal attention to the threat of these people with unemployment and precariousness, which often destabilize their lives and hinder inclusion in the local and wider community.